2002
DOI: 10.3137/ao.400208
|View full text |Cite
|
Sign up to set email alerts
|

Summer convection and lightning over the Mackenzie river basin and their Impacts during 1994 and 1995

Abstract: Lightning activity over the Mackenzie basin has been examined for the summers of 1995. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Lightning in the Edmonton region thus appears to be largely driven by annual and daily solar heating cycles. This is consistent with findings by Kochtubajda et al (2002) for the Mackenzie River basin to the north. However, Fig.…”
Section: Top Lightning Days Top Lightning Dayssupporting
confidence: 82%
See 2 more Smart Citations
“…Lightning in the Edmonton region thus appears to be largely driven by annual and daily solar heating cycles. This is consistent with findings by Kochtubajda et al (2002) for the Mackenzie River basin to the north. However, Fig.…”
Section: Top Lightning Days Top Lightning Dayssupporting
confidence: 82%
“…Space considerations forced us to truncate the far north-west section in several of the following figures. Information on lightning occurrence in portions of the Mackenzie River basin and Yukon Territory which is not shown can be found in Kochtubajda et al (2002). Figure 2 shows lightning occurrence (days yr -1 ) for February 1998 to December 2000.…”
Section: Results a Large Scalementioning
confidence: 99%
See 1 more Smart Citation
“…In northern Canada, a significant area of positive flash percentage of more than 35% extends over the forested regions of Yukon and northern British Columbia. Previous studies have suggested that thunderstorms entraining smoke from forest fires may exhibit enhanced positive CG lightning activity (Lyons et al, 1998b;Kochtubajda et al, 2002;Fernandes et al, 2006). …”
Section: Data and Analysismentioning
confidence: 99%
“…Discharges can also occur from the cloud to the sky or between clouds, but these types are less frequent (Uman, 2001). Lightning activity typically starts the majority of fires in the boreal forests of the Mackenzie Basin (Kochtubajda et al, 2002). Although fires are beneficial for controlling forest diseases and insects and for maintaining biological diversity, they affect the traditional land-based lifestyle by destroying habitat that is used for hunting, trapping, and harvesting berries and herbal medicines.…”
Section: Lightning Thunder and Firementioning
confidence: 99%